Room‐temperature‐stable diazoalkenes by diazo transfer from azides: pyridine‐derived diazoalkenes - Reitz, Justus; Antoni, Patrick W.; Holstein, Julian J.; Hansmann, Max M. (Technische Universität Dortmund, 2023)
Recently, stable diazoalkenes have received significant attention as a new substance class in organic chemistry. While their previous synthetic access was exclusively limited to the activation of nitrous oxide, we here establish a much more general synthetic approach utilizing a Regitz-type diazo transfer with azides. Importantly, this approach is also applicable to weakly polarized olefins such as 2-pyridine olefins. The new pyridine diazoalkenes are not accessible by the activation of nitrous oxide, allowing for a considerable extension of the scope of this only recently accessed functional group. The new diazoalkene class has properties distinct from the previously reported classes, such as photochemically triggered loss of dinitrogen affording cumulenes and not C−H insertion products. Pyridine-derived diazoalkenes represent the so far least polarized stable diazoalkene class reported.
Angewandte Chemie / International edition; 62(19)
Keywords: Diazoalkenes; Reactive intermediates; Diazo compounds; Vinylidenes; Nitrogen heterocycles; 540